2019
DOI: 10.1016/j.sjbs.2019.04.006
|View full text |Cite
|
Sign up to set email alerts
|

The genetic association study of TP53 polymorphisms in Saudi obese patients

Abstract: Obesity is a multifactorial metabolic disorder characterized by low grade chronic inflammation. Rare and novel mutations in genes which are vital in several key pathways have been reported to alter the energy expenditure which regulates body weight. The TP53 or p53 gene plays a prominent role in regulating various metabolic activities such as glycolysis, lipolysis, and glycogen synthesis. Recent genome-wide association studies reported that tumor suppressor gene p53 variants play a critical role in the predisp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…Elevated expression and activity of p53 was proven to occurs in the adipose tissue of obese mice [ 34 ]. In 2019, Sabir et al observed that p53 rs1042522 mutant allele is more frequent among obese individuals in Saudi population and suggested that p53 may be considered as genetic modifier for obesity development [ 35 ]. The p53 rs1042522 polymorphism (Pro72Arg) impression on body metabolism was also inspected in humanized p53 mice [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Elevated expression and activity of p53 was proven to occurs in the adipose tissue of obese mice [ 34 ]. In 2019, Sabir et al observed that p53 rs1042522 mutant allele is more frequent among obese individuals in Saudi population and suggested that p53 may be considered as genetic modifier for obesity development [ 35 ]. The p53 rs1042522 polymorphism (Pro72Arg) impression on body metabolism was also inspected in humanized p53 mice [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Elevated expression and activity of p53 was proven to occurs in the adipose tissue of obese mice (42). In 2019, Sabir et al observed that p53 rs1042522 mutant allele is more frequent among obese individuals in Saudi population and suggested that p53 may be considered as genetic modi er for obesity development (43). The p53 rs1042522 polymorphism ( Pro72Arg) impression on body metabolism was also inspected in humanized p53 mice (44).…”
Section: Discussionmentioning
confidence: 99%
“…According to our best knowledge, there is no study on association betweenTP53 rs1625895 and lipid levels. Sabir et al 2019 reported that Arg72 variant of TP53 increased BMI, W/H ratio, cholesterol, LDL level, and insulin levels (43).…”
Section: Discussionmentioning
confidence: 99%
“…The proline-to-arginine substitution can also lead to the loss of hydrophobic interactions with other amino acids. In addition, the charges possessed by mutant amino acids can cause repulsion with neighboring amino acids [21]. The electrostatic surface charge calculations also reveal that the interface of codon 72, which is equally positive and negative for proline, becomes mostly positive for arginine (Figs.…”
Section: Molecular Modeling and Electrostatic Surface Charge Calculatmentioning
confidence: 94%
“…Other SNPs, particularly those located in the DBD region of TP53, would likely better reflect variations among individual sensitivities to radiation exposure. TP53 is a well-known polymorphic gene [7], with more than 200 polymorphic variants reported in the exon, promoter, and intron regions [21]. The hotspot mutations that affect TP53 are usually located in the DBD (exons 5-8), which plays key roles in the transcriptional activation of TP53 target genes [23].…”
Section: Association Between the Pro72 Tp53 Polymorphism And Mn Formamentioning
confidence: 99%